Factors associated with COVID-19 vaccine intent among Latino SNAP participants in Southern California - Vanessa P. Scott; Sarah Hiller-Venegas; Kate Edra; Joe Prickitt; Yesenia Esquivel; Blanca Melendrez; Kyung E. Rhee (BMC, 2022)
Abstract Background COVID-19 is significantly impacting the health and well-being of the country, particularly for ethnic minority populations and low-income groups. Our goal was to determine COVID-19 vaccination intent in a low-income, Latino population receiving aid from the Supplemental Nutrition Assistance Program (SNAP) in Southern California, and identify contributing factors and concerns. Methods A cross-sectional, mixed-methods survey was conducted among participants in the Southern California Nutrition Incentives Program (¡Más Fresco! More Fresh). Only Latino respondents were included in this analysis. Primary outcome was vaccine intent trichotomized into: "definitely/likely yes", "not sure/don't know", and "definitely/likely not." Results The majority of participants (n = 486) were female (93%), Spanish speaking (74%), with a median age of 40 years (IQR = 13). Approximately half (48%) reported they would get a COVID-19 vaccine, 39% were unsure, and 13% reported "definitely/likely not". In the multivariable multinomial logistic regression model, participants with a household member with a COVID-19 health risk factor were more likely to be unsure about getting the vaccine. Participants who were primarily English speaking, did not receive the influenza vaccine last season, and reported not reading or talking about COVID-19 were more likely to report not intending to receive the vaccine. Many respondents were concerned about "side effects and ingredients", and did not trust the vaccine development process, particularly with how fast it happened. Conclusion Low-income Latinos in Southern California were generally hesitant to get a COVID-19 vaccine. Culturally sensitive vaccine promotion campaigns need to address the concerns of minority populations who experience increased morbidity and mortality from COVID-19.